Features of cardiopulmonary bypass in cardiac surgery for a child weighing 1.8 kg: a clinical case - P. V. Zinchuk; D. G. Balakhnin; A. A. Ivkin (Фундаментальная и клиническая медицина)
Aim. To demonstrate the feasibility and safety of performing cardiac surgery under cardiopulmonary bypass (CPB) in a child weighing 1.8 kg. Materials and Methods. We present a case of cardiovascular surgery under CPB in an infant with a body weight of 1.8 kg. Results. The major challenges associated with anesthetic management and CPB procedures are described, along with the strategies employed to overcome them in order to enable successful cardiac surgery. Laboratory and instrumental diagnostic indicators and vital parameters of perioperative monitoring are presented to demonstrate the safety of the procedures performed in this patient. Conclusion. Advances in current cardiovascular surgery and cardiac anesthesiology enable the performance of CPB-assisted operations in premature infants with low body weight. This article outlines the specific features of conducting cardiac surgery in a patient weighing 1.8 kg and provides evidence of its safety